Microwave-Assisted Organocatalytic Intramolecular Knoevenagel/Hetero Diels–Alder Reaction with O -(Arylpropynyloxy)-Salicylaldehydes: Synthesis of Polycyclic Embelin Derivatives - Martín-Acosta, Pedro (2016)
highly efficient and regioselective approach to new polycyclic embelin derivatives through a domino Knoevenagel condensation/intramolecular hetero Diels−Alder reaction using O-(arylpropynyloxy)-salicylaldehydes in the presence of ethylenediamine diacetate (EDDA) is reported. This organocatalyzed protocol is compatible toward a wide range of aryl-substituted alkynyl ethers with electron-donating and electron-withdrawing groups. When other active methylene compounds were subjected to this domino reaction the corresponding adducts were obtained in high yield.